Solidaritas Sosial Masyarakat Beriman di Desa Penambuhan Kabupaten Pati Pada Masa Pandemi COVID-19 - Prastika, Jasmiatun Lynnda; Farihah, Irzum (Advances in Humanities and Contemporary Studies, 2023)
The phenomenon during the COVID-19 pandemic experienced by the community is influential in life, especially social conditions facing change. This phenomenon is found in the faithful community of Penambuhan Margorejo Pati Village during the COVID-19 pandemic which experienced a reduction in social solidarity. The purpose of this article is to describe and find out the social solidarity that occurred in Penambuhan Village during the COVID-19 period. This study uses a qualitative method, where the researcher conducts interviews with the people concerned, such as people who are exposed to COVID-19, people who are not exposed, families of patients with COVID-19, and community leaders in Penambuhan Village. The results of the study focus on two important points. First, the views of the faithful regarding social solidarity in Penambuhan Village during the COVID-19 pandemic. There has been a lack of social solidarity in the community of faith, where people who have been exposed to COVID-19 are shunned and even ostracized by their neighbors. As a community of faith, we should help each other to our fellow human beings as a form of acts of faith. Second, the main cause of the problem of social solidarity of the faithful in Penambuhan Village during the COVID-19 pandemic, namely the negative stigma from the community regarding COVID-19, a very dangerous type of virus that can cause death. In addition, people who are not exposed to COVID-19 stay away from people who are exposed because they have excessive anxiety and are very afraid of contracting it.